The Motivation of Choosing Midwifery Field of Study and Related Factors among the Midwifery Students of Islamic Azad University Rasht Branch Iran - Shiva Alizadeh; Mojgan Sigarchian (Kerman University of Medical Sciences, 2013)
Background & Objective: Motivation is the driving force beyond all human activities Without motivation human species are not capable of implementing any planned activity The more ones motivation is in line with her interests and skill sets the higher chance the individual has to achieve success in her professional and educational endeavors This study was performed to determine midwifery students motivation and related factors about their field Methods: This descriptive crosssectional study was conducted on all midwifery students who were studying at Islamic Azad University of Rasht in the first semester of academic year 20112012 The information was gathered through a questionnaire which has two parts personal information and questions about motivation for choosing field of study The data was analyzed by SPSS software version 16 using descriptive and analytical statistics Results: The mean score of students motivation for choosing field of study was 4985 ± 614 which was higher than the acceptable score There no significant relationship between score of motivation and research variables (job and education of parents marital status and university entry quotas living place diploma score economic situation and students age) Conclusion: Our research shows that the students of midwifery are highly motivated and have great enthusiasm for studying this academic discipline Therefore it is imperative for the authorities to seize this opportunity and make an allout effort to improve the educational standards of promising students in order to maximize their productivity